2016
DOI: 10.1007/s12161-016-0550-2
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Profile and 87Sr/86Sr Isotope Ratio as Fingerprints for Geographical Traceability of Wines: an Approach on Romanian Wines

Abstract: Wine geographical traceability is an important topic in the context of wine authentication and for that, many researchers worldwide have addressed this subject by developing different methodologies based on multivariate analysis of natural chemical composition data (inorganic or organic parameters) and isotopic signature. The goal of this work was to assess the potential of elemental composition and strontium isotope ratio ( 87 Sr/ 86 Sr) of wines from important wineproducing regions in Romania, located in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…The accuracy of the methods was evaluated by replicate analyses of known concentration samples (between 10 µL to 10 mL concentrations) and the obtained values ranged between 0.8-13.1 percent, depending on the element. The global recovery for each element was estimated and the obtained values were between 84.6-100.9% (Geana et al, 2016).…”
Section: Reagents and Solutionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The accuracy of the methods was evaluated by replicate analyses of known concentration samples (between 10 µL to 10 mL concentrations) and the obtained values ranged between 0.8-13.1 percent, depending on the element. The global recovery for each element was estimated and the obtained values were between 84.6-100.9% (Geana et al, 2016).…”
Section: Reagents and Solutionsmentioning
confidence: 99%
“…Several studies on its use for wine geographical origin assessment can be found in literature (Horn et al, 1993;Almeida and Vasconcelos, 2004;Durante et al, 2013;Catarino et al, 2016). Recently, within a research program regarding strategies for wine fingerprinting, the authors confirmed 87 Sr/ 86 Sr as a viable tool for traceability of Romanian PDO and GI wines (Geana et al, 2016), Portuguese PDO, where soils were developed on different geological formations (Martins et al, 2014;Catarino et al, 2016). The use of this parameter as a marker of wine geographical origin is based on the assumption that a relation between soil, plants and wine exists.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations